Economics of land degradation: The costs of action versus inaction - Nkonya, Ephraim M.; Gerber, Nicolas; von Braun, Joachim; De Pinto, Alessandro (International Food Policy Research Institute, 2011)
In recent years, prices of agricultural land have increased quickly, actually doubling and tripling in many parts of the world. This land value reassessment has been prompted by rising crop prices and perceived land scarcity. But even as the value of land rises, land degradation continues and investments to prevent it are lagging. Awareness of environmental risks has moved to the forefront of global consciousness during the past 25 years. However, this awareness has not translated into comprehensive action to address the problem of land degradation, which poses a serious threat to long-term food security. This inaction is primarily the result of limited knowledge of the costs related to land degradation and of insufficient institutional support. Policy action and research are needed to resolve this paradox of high-value land and low levels of investment.